Efektivitas Hak Bekerja Bagi Penyandang Disabilitas Fisik Di Kabupaten Jember - Achmad Hasan Basri; Ibnu Al Alwaton Surya Waliden; Elizatul Mufidah Indana (Fakultas Hukum Universitas Islam Jember, 2025)
This study aims to examine the effectiveness of fulfilling the right to work for people with disabilities in Jember Regency. The method used is empirical legal research using a legislative approach and legal sociology. The results of this study: 1. The effectiveness of the right to work for people with physical disabilities in Jember Regency has not been effective due to several factors, namely: There is no discretion regarding the optimization of the right to work for people with disabilities in the private employment sector by law enforcement. There are no special training program facilities for people with disabilities. The community in viewing the existence of people with disabilities still judges from their limitations. As well as cultural factors where there is a stigma against people with disabilities who consider their physical limitations. 2. Some of the obstacles faced by the Jember Regency Regional Government are as follows: low awareness of the importance of inclusion for people with disabilities, limited accessibility, lack of training, negative social stigma in society, support from the Regional Government in incentive policies to encourage companies to employ people with disabilities. Data is not yet accurate and the lack of information on job opportunities reduces the participation of people with disabilities.